International differences in the family gap in pay: the role of labor market institutions - Arnaud Dupuy; Daniel Fernández-Kranz (Institute for the Study of Labor (IZA), 2007)
Using microdata for 35 countries over the period 1985-1994-2002 we find that labor market institutions traditionally associated to more compressed wage structures are associated to a higher family gap. Our results indicate that these policies reduce the price effect of having children but aggravate the human capital loss due to motherhood. We also find evidence that policies that help women continue in the same job after childbirth decrease the family gap. Of all the countries we study, mothers in Southern Europe suffer the biggest family gap and our analysis indicates that this is due to the bad combination of labor market policies in these countries. Our results are robust to specification changes and indicate that the main reason mothers lag behind other women in terms of earnings is the loss of accumulated job market experience caused by career breaks around childbirth.
urn:nbn:de:101:1-20080402555
Keywords: 330; Lohndifferenzierung; Familienökonomik; Frauenarbeitslohn; Arbeitsmarktpolitik; Institutionalismus; OECD-Staaten